The profile of Sociology teachers of the 6th Gerencia Regional de Ensino-O perfil dos professores de Sociologia da 6ª Gerencia Regional de Ensino - Dijací Nogueira; Cléa Carneiro Palmeira Rêgo (Diversitas Journal, 2020)
This study aimed to analyze the recent process of institutionalization of sociology teaching in Brazil, especially in the school context; The teaching didactic every day; The profile of the professor of sociology and those of the Sixth Gerência Regional de Ensino de Alagoas (6th GERE). For the accomplishment of this research, questionnaires with closed questions to thirteen teachers of the sociological area were elaborated to better systematize and problematize the teaching/learning of sociology and the profiles of these professionals of the education. For this, this work is inserted in a descriptive research approach that has as characteristic not only to describe certain phenomena in relation to age, gender, ethnicity, social class, but also to interpret such implications. In addition, bibliographic research on the topic was also used. After that, after collecting and processing the data, it was possible to know and reveal the nuances about the answers given by the teachers participating in this research, because in this way we were able to characterize their profiles. Therefore, the analyzes showed that these profiles are in permanent construction due to the social, political and economic conjuncture, being, thus, in constant social transformation.